A comparison of PC oxidation products as detected by MALDI-TOF and ESI-IT mass spectrometry. (March 2017) - Engel, Kathrin M.; Schiller, Jürgen
Highlights: (Phospho)Lipid oxidation is a physiologically very important process. PC 16:0/18:1 and PC 16:0/18:2 were oxidized by sodium permanganate. Soft ionization mass spectrometry (MALDI and ESI) was used to detect the generated lipid oxidation products. Chain-shortened products (such as aldehydes and carbxylic acids) could be detected by both methods. In contrast, primary products such as hydroperoxides are preferentially detected by ESI MS. Abstract: Oxidized (phospho)lipids are of paramount interest for different reasons: besides their in vivo relevance as markers of inflammatory diseases, they are often needed in the laboratory to study the response of selected cells to oxidized lipids. Mass spectrometry (MS) is nowadays one of the most powerful methods to identify lipid oxidation products. Although MALDI and ESI MS are both widely used, it is so far not clear whether all potential phospholipid oxidation products can be detected by both methods This aspect will be studied here using NaMnO4 -oxidized phosphatidylcholine 16:0/18:1 and 16:0/18:2 as simple, but reliable model systems. We will show that chain-shortened products such as aldehydes and carboxylic acids (generated by cleavage at the double bond position) can be easily detected by both ionization methods: without the need of any derivatization. However, primary oxidation products such as hydroperoxides can be predominantly detected by ESI MS while MALDI-TOF MS detects secondary oxidation products derived thereof more sensitively. Potential reasons for these differences will be discussed and put in the context of biological mixture analysis.